Performance of Thermal Comfort in Modern Glass Façade Building in Universiti Teknologi Malaysia Kuala Lumpur (UTM KL) - ZAMZURI, NUR HANIS NATASYA; ROSLAN, NURUL HIDAYAH (Progress in Engineering Application and Technology, 2025)
This study investigate the thermal comfort performance of modern glass facade building at Universiti Teknologi Malaysia (UTM) Kuala Lumpur in tropical climate. Glass facade enhance aesthetic and natural lighting but often contribute to exceesive heat gain and reducing thermal indoor comfort. The research utilizes EnergyPlus simulation software used to measure key parameters such as air temperature, mean radiant temperature, Predicted Mean Vote (PMV), and Predicted Percentage of Dissatisfied (PPD) were  analyzed. Result reveal that optimized window-to-wall ratio designs and glazing material can significantly enhance thermal comfort in the building. This findings provide practical recommendations for facade glass design in tropical climates. This study contributes valuable design strategies that combine advanced glazing materials, optimal WWR configuration and effective shading solution to achieve the thermal comfort performance.